Gendered Violence Jewish Women in the Pogroms of 1917 to 1921 - Astashkevich, Irina (Academic Studies Press, 2018)
This is a groundbreaking study of an important and neglected topic-the systematic use of rape as a strategic weapon of the genocidal anti-Jewish violence, known collectively as pogroms, that erupted in Ukraine in the period between 1917 and 1921, and in which at least 100,000 Jews died and undocumented numbers of Jewish women were raped. The book is based on the in-depth study of the scores of narratives of Jewish men and women who survived the pogrom violence, but were then all but forgotten for almost a century. This book deconstructs the motives of perpetrators, the experience and expression of trauma by the victimized community, and how the genocidal objectives of the pogrom perpetrators were achieved and maximized through the macabre carnival of violence.